Situs Ingatan : Tugu Penembakan Tentara (NICA) Pada Masa Revolusi Fisik 1947 Di Desa Banjar Asem, Seririt, Bali Serta Potensinya Sebagai Sumber Belajar Sejarah Di SMA. - Wahyu, Lugas Tri Wahyu; Arta, Ketut Sedana Arta; Martayana, I Putu Hendra Mas Martayana (Widya Winayata : Jurnal Pendidikan Sejarah, 2025)
This study aims to determine the historical background of the NICA army shooting memorial in Banjar Asem Village along with the values ​​of struggle contained during the struggle of the Banjar Asem youth during the Physical Revolution period and its use as a source of learning history in high school. The author uses a qualitative historical research method consisting of four stages, namely heuristics, source criticism, interpretation and historiography. The results of this study indicate that the Banjar Asem Village memorial was built to commemorate the incident of blocking one of the NICA generals carried out by a group of Banjar Asem youth who defended the republic during the Physical Revolution in 1947. This is related to the conditions in Bali, especially after the Denpasar conference which made the youth who defended the republic increasingly pressured and Bali experienced a lot of political turmoil. There are several values ​​that can be taken from the struggle of the Banjar Asem youth and can be used as a supplement to teaching materials on the history of the Physical Revolution in a local context at the high school level. The history of the Banjar Asem Village memorial monument can be used as a source for learning history in Phase F (grade 11) semester 2 in the material "The Struggle to Defend Indonesian Independence" which can later be connected to the events of Bandung Lautan Api, Puputan Margarana, the Battle of Surabaya and others. Keywords: Memorial Monument, Learning Resources, Struggle Values, Physical Revolution